Issues covered in ’My 2 innings’: A discussion from my personal perspective - Shankar, PR (Journal of College of Medical Sciences-Nepal, 2010)
DOI: 10.3126/jcmsn.v6i3.4081 Journal of College of Medical Sciences-Nepal, 2010, Vol. 6, No. 3 pp.68-71